Kingship, lordship, and resistance: a study of power in eleventh- and twelfth-century Ireland - MULHAIRE, RONAN JOSPEH (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2020)
This thesis starts from the premise that historians of medieval Ireland have interpreted 'power' in a very narrow way. Engagement with the rich corpus of international literature on power reveals the sheer complexity and vicissitudes of 'power' as a concept, and forms the launching-pad for the thesis as a whole. From there, the broader issue of resistance is discussed, in particular the phenomena of regicide and revolt - how did resistance manifest itself, and in particular violent resistance? It is suggested that we actually see a decline in the number of regicides between the battle of Clontarf and the English invasion. Connected is the position of non-royal lordship. It has commonly been argued that petty kings were being downgraded to mere 'lords'. This thesis argues that there is no sound evidential basis for this oft-propounded trope, and therefore a posited decline in regicides cannot be explained away by this old argument. The thesis argues that the relationship between non-royal lords and their social inferiors is being reconfigured; a new interpretation is put forward for the emergence of 'baile', and it is likely significant that this coincides with the upsurge in references to 'lords' in the chronicles. Finally, the little-studied phenomenon of revolt is explored at two levels - revolts against the rule of an individual king, and what we might term 'popular' revolts. As regards the first level, much of the discussion revolves around revolts denoted in the annals by the verbal-noun imp?d. It argues that the adoption of a new term, coupled with the decline in regicides over time suggests two things: that patterns of resistance were changing in the century and a half between Clontarf and the invasion, and that the ways in which resistance were being thought about was also evolving. As regards social antagonisms and the like, chapter four concludes that patterns of popular unrest in pre-invasion Ireland bore remarkable similarity to elsewhere in Europe in this period.
APPROVED
Keywords: Eleventh century; Twelfth century; Power; Kingship; Lordship; Resistance; Revolt; Medieval Ireland; Regicide; Baile; High-kingship; Imperator; Violence